Animal Bones Char Solubilization by Gel-Entrapped Yarrowia lipolytica on Glycerol-Based Media - Maria Vassileva; Bettina Eichler-Lobermann; Antonia Reyes; Nikolay Vassilev (The Scientific World Journal)
Citric acid was produced with free and k-carrageenan-entrapped cells of the yeast Yarrowia lipolytica in single and repeated batch-shake-flask fermentations on glycerol-based media. Simultaneous solubilization of hydroxyapatite of animal bone origin (HABO) was tested in all experiments. The highest citric acid production by free yeast cells of 20.4 g/L and 18.7 g/L was reached after 96 h of fermentation in the absence and presence of 3 g/L HABO, respectively. The maximum values for the same parameter achieved by gel-entrapped cells in conditions of single batch and repeated-batch fermentation processes were 18.7 g/L and 28.1 g/L registered after 96 h and the 3d batch cycle, respectively. The highest citric acid productivity of 0.58 g L−1 h−1 was obtained with immobilized cells in repeated batch mode of fermentation when the added hydroxyapatite of 3 g/L was solubilized to 399 mg/L whereas the maximum efficiency of 89.0% was obtained with 1 g/L of HABO.